COVID-19 MENGGUNCANG PERUSAHAAN BATUBARA DI BEI: EKSPLORASI PERAN LEADERSHIP CEO DAN IN/EX COMPANY ENVIRONMENT - Iswahyudi; Suyanto; Darmansyah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The Indonesian government has taken numerous measures to respond the COVID19 pandemic. This policy was taken caused the stock market slowed down of coal mining companies on IDX due to COVID-19 pandemic. This study aims to examine the impact of the COVID-19 on stock return as measured by leaderships CEO (SIM and SGM), company performance (DER, ROA and EPS), technical factors (IIA) and dividend policy as moderation. This research use quantitative method and data analysis was conducted by moderated regression analysis (MRA). Based on 17 samples, it shows that directly only the DER, ROA and IIA variables have significant on stock return, while the SIM, SGM and EPS variables have no significant on stock return. indirectly the DER variable which is moderated by dividend policy has significant on stock return or means that the dividend policy strengthens the relationship between DER and the stock return (quasi moderation).